2016
DOI: 10.1007/s12564-016-9415-z
|View full text |Cite
|
Sign up to set email alerts
|

Adopting self-accreditation in response to the diversity of higher education: quality assurance in Taiwan and its impact on institutions

Abstract: In 2012, Taiwan implemented a dual-track quality assurance system comprising accreditation and selfaccreditation in higher education institutions. Self-accrediting institutions can accredit their programs without requiring approval from external quality assurance agencies. In contrast to other countries, the Ministry of Education of Taiwan authorized self-accrediting institutions to develop their own evaluation standards. This study investigated the institution-based accreditation standards and their implicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 17 publications
0
3
0
1
Order By: Relevance
“…To ensure the integrity and autonomy of the institutions, self-assessment processes and mixed systems have been incorporated so that both self-evaluation and external evaluation are considered (Brennan and Shah, 2000;Vanhoof and Van Petegem, 2007). In many countries, self-accreditation processes are being implemented (Chen and Hou, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…To ensure the integrity and autonomy of the institutions, self-assessment processes and mixed systems have been incorporated so that both self-evaluation and external evaluation are considered (Brennan and Shah, 2000;Vanhoof and Van Petegem, 2007). In many countries, self-accreditation processes are being implemented (Chen and Hou, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Las líneas temáticas establecidas en el estudio permitieron reconocer los ejes desde donde se fundamentan los procesos de aseguramiento de calidad, se reconoce el valor de las políticas de educación y los estándares de calidad nacional como guía para la inclusión y adopción de parámetros estratégicos. En ese mismo orden de ideas, Du et al, (2017) mencionan que los marcos de control de calidad y los procesos de integración global en la práctica internacional forman parte de un sistema nacional para garantizar la calidad de la educación, en concordancia, Cardoso et al (2017) sugieren que los marcos de control de calidad podrían, por lo tanto, moverse de un enfoque más prescriptivo a uno más interpretativo, es decir, más dependiente de la interpretación y adaptación de las instituciones; las modificaciones se deben considerar para ajustar los sistemas de garantía de calidad y buscar, simultáneamente, la excelencia estableciendo un equilibrio entre la responsabilidad y la autonomía para todas las partes interesadas de la educación superior (Chen y Hou, 2016). Se puede distinguir que la predisposición de las IES por garantizar el aseguramiento de calidad en sus procesos ha sido tomando como referencia estándares que sistematizan las experiencias de la aplicación de sistemas de calidad, en donde estos lineamientos han sido creados en diferentes contextos y adaptados según las variables del entorno de la institución, aunque estas características promueven el desarrollo de trabajo de experiencias sobre el aseguramiento de la calidad educativa, es necesario garantizar la vinculación de variables que den cuenta de las oportunidades de mejora que pueden existir en el proceso enseñanza-aprendizaje.…”
Section: Discussionunclassified
“…Taiwan also possesses advanced e-learning technology and has expanded all or part of the English curriculum in order to make the business educational system more attractive and accessible to international students. Although quality assurance mechanisms have been established in Taiwanese business education [12,45], many universities offer programs in cooperation with global universities; hence, many talented international students may initially be attracted to Taiwan based on these partnerships. It is imperative to note that the participants in Conception C suggested that there should be a proper balance in the curriculum design between local features and international perspectives, which is consistent with the studies of Ma and Trigo [46].…”
Section: Discussionmentioning
confidence: 99%